Legal Review of The Determination of The Estimated Price As A Basis For Calculation of The Cost of Acquisition of Rights To Land and Buildings In The Sale and Purchase of Land and Buildings In Karawang Regency - Dede Nurhayatie; Rahmatiar, Yuniar; Abas, Muhamad (Journal of Law, Politic and Humanities, 2024)
The reciprocal relationship established by humans involves engaging in legal transactions, such as buying and selling. According to the provisions of the prevailing laws and regulations in Indonesia, any transfer of rights to land and/or buildings is subject to taxation. Article 87, paragraph (1) of Law Number 28 of 2009 concerning Regional Taxes and Levies (commonly referred to as UU PDRD) stipulates that the basis for calculating the Acquisition Fee for Rights to Land and/or Buildings (BPHTB) is the Tax Object Acquisition Value (NPOP). The issue at hand pertains to how the appraised price is determined as the basis for calculating the acquisition costs of rights to land and buildings in land and building transactions within the Karawang Regency. The legal consequences of setting the appraised price as the basis for calculating these costs are as follows: Uncertainty in Calculation and BPHTB Amount: The lack of clarity in determining the appraised value may lead to uncertainty in calculating the BPHTB amount. Legal Consequences: Incorrectly assessing the appraised value can render the transaction invalid and void. Legal Violations: Failure by taxpayers to use the appropriate basis for assessment constitutes a legal violation. The qualitative research method employed in this study utilizes a Normative Juridical approach. Based on Law Number 28 of 2009, the Acquisition Fee for Rights to Land and Buildings has officially become a local tax. The purpose of transferring this fee is to enhance regional autonomy and support financial management for regional development.